Proses Pengurusan Penggantian Crew Kapal pada Kantor KSOP Dumai oleh PT. Samudera Sarana Karunia Dumai - Fujayani Munthe; Yuna Sutria (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This paper aims to determine the process of managing ship crew at the Dumai KSOP Office by PT. Samudera Sarana Karunia Dumai is a company that operates in the shipping agency sector, which provides services for permits for entry and exit of ships, permits for entry and exit of foreign crew to Indonesia. The data collection method is the field observation method (field research) and the library research method to find out more closely how the Company PT. Samudera Sarana Karunia Dumai and carries out crew document management activities according to the crew's needs. The process of arranging the replacement of the ship's crew at the KSOP office (Port Authority Harbor Master's Office) goes through a process that must be carried out by the agent assigned to the Owner. In the process of signing on the seafarer's book, the ship's crew must complete all related documents. This is done so that a seafarer is legally and absolutely on board the ship in accordance with the maritime work agreement of a ship's seafarer and the seaman's book is signed first by the official Harbor Master, as well as the management of the seaman's book. signing off the sailor's book for the ship's crew. The process of signing off the seaman's book is carried out if there is a ship's crew who will work on the ship or stop. Apart from that, the sign off of the seafarer's book is also carried out on the basis of a change of ship's crew where the ship's crew contract period has ended.